Atypical formation of pericallosal artery A4 segment altering the corpus callosum - Anatomical case report - Andrzej Żytkowski; Agata Mazurek; Andrzej Dubrowski; Edward Clarke; Karolina Barszcz; Krzysztof Balawender; Bartosz Szmyd; Maciej Radek (Elsevier, 2022)
Background: The pericallosal artery (PrcA) can be referred to as a segment of the anterior cerebral artery that extends from the origin of the callosomarginal artery along the callosal sulcus to the splenium of the corpus callosum. Methods: This report presents an atypical morphology of the pericallosal artery A4 segment modifying the macroscopic structure of the corpus callosum. No similar case was found in the medical literature. Therefore, this report aims to present the PrcA anatomical anomaly of potential clinical significance. Case description: During routine dissection of the human brain, bilateral atypical formation of pericallosal artery A4 segment was found. The anomaly was that the artery formed a loop that altered brain tissue with hollow formation within the corpus callosum trunk. The atypical loop of the pericallosal artery gave off the long callosal artery on both sides. Conclusions: Arterial anomalies can alter the brain tissue. Thus anatomical studies on various anomalies can be significant from the clinical point of view.